e-Learning Experiments - the software RACE and the general design - Rockmann, U.; Thielke, S.; Seyda, M. (International Journal of Computer Science in Sport, 2003)
The article introduces to the hypermedia learning-software RACE. RACE was developed within the framework of the research project "New Learning Technologies" (1994-2002) in order to carry out e-learning experiments (supported by the German Federal Institute for Sport Science BISp VF 0407/13/01/2001). Additionally, the general basic research design is described. All investigations that used RACE as software, were based on this design. The specific research questions, special design variations, and results are presented in detail in the articles by ROCKMANN, THIELKE & SEYDA in this journal.